Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12933-020-01092-7
|View full text |Cite
|
Sign up to set email alerts
|

Growth differentiation factor-15 is associated with cardiovascular outcomes in patients with coronary artery disease

Abstract: Background: Growth differentiation factor-15 (GDF-15) is a marker of inflammation, oxidative stress and it is associated with adverse prognosis in cardiovascular disease. The aim of the present cohort study is to investigate the prognostic value of GDF-15 in patients with coronary artery disease (CAD) during long-term follow up. Methods: A total of 3641 consecutive patients with CAD were prospectively enrolled into the study and followed up for major adverse cardiovascular events (MACEs) and all-cause death up… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Growth differentiation factor 15 (GDF-15) belongs to the transforming growth factor-β (TGF-β) superfamily, previously known as the macrophage-inhibiting cytokine, which increases as a consequence of inflammation and oxidative stress [ 22 ]. Because atherosclerosis is an inflammatory process, it has been hypothesized that GDF-15 may be used as a valid marker of prognosis in patients with atherosclerosis-related CVD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth differentiation factor 15 (GDF-15) belongs to the transforming growth factor-β (TGF-β) superfamily, previously known as the macrophage-inhibiting cytokine, which increases as a consequence of inflammation and oxidative stress [ 22 ]. Because atherosclerosis is an inflammatory process, it has been hypothesized that GDF-15 may be used as a valid marker of prognosis in patients with atherosclerosis-related CVD.…”
Section: Resultsmentioning
confidence: 99%
“…Because atherosclerosis is an inflammatory process, it has been hypothesized that GDF-15 may be used as a valid marker of prognosis in patients with atherosclerosis-related CVD. Recently, an observational cohort study evaluated the prognostic value of plasma GDF-15 in 3641 patients with CAD, who were followed up for 5.3–7.6 years [ 22 ]. In this study, elevated GDF-15 levels > 1800 ng/L were independently associated with the primary endpoint (composite of all-cause mortality, ACS, or unplanned coronary revascularization) and all-cause mortality [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…GDF-15 is increased in response to cardiac damage and the inflammatory process, thereby increasing the risk of an elevated cardiovascular event [ 177 ]. In the presence of an ACS, a single measurement of GDF-15 and concentrations greater than 1800 ng/L were linked to an elevated risk of all-cause mortality, MACEs and hospitalization for heart failure, but not subsequent readmission for MI [ 178 , 179 ]. Additionally, GDF-15 concentrations were assessed at baseline in 4330 patients, and the same cut-off value was linked to a twofold increase in the risk of CV death/HF [ 180 ].…”
Section: Resultsmentioning
confidence: 99%
“…Myocardial ischemia induced by coronary atherosclerosis or microcirculation dysfunction is tightly associated with heart structure and function. Several observational studies showed that GDF-15 concentration was continuously associated with the risk of coronary heart disease (33,34). Our data suggest that GDF-15 is a strong predictive factor of the mortality of CHF with ischemic etiology.…”
Section: Discussionmentioning
confidence: 99%